황해상 덕적도의 대기 에어로졸 특성 - 이승복; 배귀남; 김용표; 진현철; 윤용석; 문길주 (한국대기환경학회, 2002)
Various air pollutants were measured at Tokchok Island in the Yellow Sea that is about 50 km distant fromIncheon since April 1999. This study was undertaken to help understanding the level of air pollution and itsdistribution characteristics over the Yellow Sea. The geographical characteristics of the air pollution monitoringstation and emission inventories of Tokchok Island are introduced. The mass concentrations and chemicalcompositions of TSP and PM2.5concentrations are about 37.2g/m3 for TSP and 18.7g/m3 for PM2.5, respectively, which are similar to or a littlelower than the values observed in other background sites at Kangwha and Taean. However, they are much lowerthan those observed at Qingdao in China.The low mass concentration and major anthropogenic ion concentrations in aerosols collected at Tokchok Islandnon-sea-salt sulfate to the total sulfate concentration of TSP and PM2.5 are greater than 80% for both sizes. Ithence suggests that the sulfate be mainly affected by anthropogenic sources. If we consider the average mass ratioof PM2.5to TSP, the mass fractions of anthropogenic species to PM2.5, and the molar ratio of nss SO42- to totalNO3-, it may be possible to infer that a part of anthropogenic species measured at Tokchok Island be transportedfrom China. The characteristics of neutralization of nss SO42- and the particle size of major ions are also discussed.